Ylide‐Functionalized Phosphines: Strong Donor Ligands for Homogeneous Catalysis. Issue 39 (25th June 2018) - Scherpf, Thorsten; Schwarz, Christopher; Scharf, Lennart T.; Zur, Jana‐Alina; Helbig, Andreas; Gessner, Viktoria H.
Abstract: Phosphines are important ligands in homogenous catalysis and have been crucial for many advances, such as in cross‐coupling, hydrofunctionalization, or hydrogenation reactions. Herein we report the synthesis and application of a novel class of phosphines bearing ylide substituents. These phosphines are easily accessible via different synthetic routes from commercially available starting materials. Owing to the extra donation from the ylide group to the phosphorus center the ligands are unusually electron‐rich and can thus function as strong electron donors. The donor capacity surpasses that of commonly used phosphines and carbenes and can easily be tuned by changing the substitution pattern at the ylidic carbon atom. The huge potential of ylide‐functionalized phosphines in catalysis is demonstrated by their use in gold catalysis. Excellent performance at low catalyst loadings under mild reaction conditions is thus seen in different types of transformations. Abstract : YPhos : The ylide‐functionalized phosphines (YPhos), a novel class of strong donor ligands, are readily accessible from commercially available starting materials and exhibit easily tunable electronic and steric properties. The huge potential of these ligands in catalysis is demonstrated by their use in gold catalysis, with excellent performance observed at low catalyst loadings under mild reaction conditions.